A Molecular Dynamics Study of the Mechanical Properties of Ionic Copolymers during Tension–Recovery Deformation. Issue 2 (16th November 2020) - Ma, Mengze; Fu, Yao
Abstract: Polymer electrolytes have attracted ever‐increasing attention in the field of energy storage and conversion due to their significantly improved safety features and processability compared with liquid electrolytes and inorganic solid electrolytes. The mechanical integrity of ionic copolymers is one of the most important properties that need to be considered in the development of polymer electrolytes. In this study, the uniaxial tension–recovery studies are conducted in single‐ion diblock copolymers via coarse‐grained molecular dynamics simulation, where the fraction of the charged block is varied to form spherical, cylindrical, and lamellar morphologies. It is found that the dynamic hysteresis loss and permanent displacement have strong dependence on the fraction of the charged block and charge ratio. The change in the radius of gyration greatly varies for the different morphology. Furthermore, the charged copolymers are subjected to more changes in bond orientation during tension and also preserve more changes at recovery. It is likely that the charged monomers and counterions contribute to the stronger crosslinking effect in charged copolymers, reducing chain slippage and hysteresis loss. Abstract : Tension–recovery studies are conducted in diblock copolymers to understand the dynamic hysteresis loss and permanent displacement. The configurational change including bond orientation and radius of gyration is analyzed during the deformation process and is found to strongly depend on the volume fraction of the charged block and charge ratio.